Capital structure determinants for family business in MENA region - Ismail, Wedad (AUC Knowledge Fountain, 2017)
The aim of this thesis is to explore the determinants of capital structure of listed firms in the Middle East and North Africa. There is a large strand of literature that explains capital structure decisions in firms with the main theories explaining financing choices being: Pecking Order theory, Trade-off theory, Agency theory. The main contribution of the thesis is to explore whether family ownership concentration influences the capital structure. Family Owned businesses constitute around 22% of all business in the MENA region and the effect of such ownership structure on financing decisions has not been explored. The thesis relies on hand collected cross sectional data for 2015 a sample of firms from the region where family ownership ranges from 10% to 90%. The main methodology involves estimating a model, similar to previous papers’, where leverage is the dependent variable and family ownership, profitability, growth, size, tangibility, non-debt tax shield, and other institutional and macroeconomic factors are independent variables. The main result of the thesis are that family ownership concentration has no effect on the capital structure decisions showing that financing decisions do not vary between family and non-family owned business. The Pecking Order Theory seems to explain the managers’ behaviour of these firms from 11 MENA countries with five GCC economies, with negative influence of profitability and liquidity on leverage.